Between Philosophy and Literature: Albert Camus and the Transition of Absurd Existence towards the Community of Solidarity - Buceta, Martín (2022)
In his Carnets Camus affirmed that we only think by the image, so the philosopher must write novels. This assertion is largely noted in Camus' philosophical-literary project. It is possible to find in his written production a fluctuation in which philosophical works are mirrored with novels that place the problems in a literary way. In the particular case of The Rebel what can be found is an explanation of certain images offered by him earlier in The Plague and The State of Siege. In this article, the aim is to explore the philosophical itinerary of Camus that leads him to make a transition from the consideration of the absurd existence, typical of The Myth of Sisyphus and The Stranger, towards the postulation of a solidarity community that recognizes a human nature, which occurs in The Rebel, The Plague and The State of Siege.